Formulation and Characterization of Nigella Sativa Niosomal Gel for Topical Application - Dr.C.Rubina Reichal; N.Subramanian; M.Sangeetha; S.Manju; M.Shobana (International Journal of Pharma and Bio Sciences, 2022)
Niosomes play an important role in novel drug delivery systems and it can increase the bioavailability and modify the pharmacokinetic property of drug.Topically used niosomal formulations increase the residence time and decrease the systemic circulation . The core objective of the study is to formulate the Nigella sativa niosomes for topical application. The niosomes of Nigella sativa was prepared by hand shaking method with various ratios of cholesterol and span. The formulated niosomes were characterized by Size, Shape, Entrapment efficiency, in-vitro drug release study, release kinetics study and Anti microbial activity. TEM study analyses showed that the formulated niosomes were spherical in shape. Among the formulations, formulation 5 (F5) showed a 98.99% cumulative percentage of drug release at the end of 24thhr. The in vitro release profile of optimized formulation5 (F5) was fitted with various kinetic equations and it was best fit with zero order kinetics and the korsmeyer model explained the release pattern of the drug and it followed the non fickian diffusion. The optimized formulation (F5) was effective against P. aeruginosa. The best formulation was selected based on the evaluation parameters and it is more stable. The Nigella sativa niosomal gel was formulated by incorporating the optimized formulation with carbopol. The carbopol was selected for this formulation, because of its hydrophilic nature and also to improve the residence time of the drug at the absorption site of the skin . The prepared gel was evaluated for physical appearance, pH, Rheological study, Drug content and Stability studies. From the study, it was concluded that the prepared niosomal gel may be enhancing the penetration of drug and providing a sustained pattern of drug release for topical application and to improve the antimicrobial activity.